Psychological hallmarks of skilled golfers - Hellstöm, J. (Sports Medicine, 2009)
In this article, the psychological hallmarks of skilled golfers (professionals and amateurs with handicaps of =4) are investigated. Professional golfers believe that attitude, desire and motivation are important psychological qualities necessary to succeed in tournaments. They are committed to golf, have goals they strive for, make plans, evaluate their performance and systematically train towards improving their game. The study of skilled golfers' traits, as measured by 16 personality factors, has provided ambiguous results and there may be more complex associations not yet investigated in golf.